2009
DOI: 10.3766/jaaa.20.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Speech Rate, Background Noise, and Simulated Hearing Loss on Speech Rate Judgment and Speech Intelligibility in Young Listeners

Abstract: These findings can be used to support the need for counseling patients and their families about the potential advantages to using average speech rates or rates that are slightly slowed while conversing in the presence of background noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…One such strategy is for a communication partner to slow their speaking rate. As suggested by Adams and Moore (2009), even slowing from a fast speaking rate to a more normal rate may be of benefit for hearing impaired patients. The present study provides support for this recommendation as listeners in the present study were willing to cope with more background noise in environments with slow and normal speech rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such strategy is for a communication partner to slow their speaking rate. As suggested by Adams and Moore (2009), even slowing from a fast speaking rate to a more normal rate may be of benefit for hearing impaired patients. The present study provides support for this recommendation as listeners in the present study were willing to cope with more background noise in environments with slow and normal speech rates.…”
Section: Discussionmentioning
confidence: 99%
“…Speech can be temporally distorted through rate-alteration *University of South Alabama, Mobile, AL Corresponding author: Shelby Tiffin, Department of Communication Sciences and Disorders, Missouri State University, Springfield, MO 65897; Email: shelbytiffin@missouristate.edu of speech (time compressed or expanded) or the addition of reverberation. Speech perception and speech understanding (in quiet and in noise) have been measured using rate-altered speech in younger and older adults (Gordon-Salant and Fitzgibbons, 1993;Vaughn and Letowski, 1997;Gordon-Salant and Fitzgibbons, 1999;Adams and Moore, 2009;Adams et al, 2012). Several studies have demonstrated that older adults struggle with understanding rapid speech (Wingfield et al, 1985;Gordon-Salant and Fitzgibbons, 1993;Wingfield et al, 1994;Wingfield, 1996;Vaughan and Letwoski, 1997;Gordon-Salant et al, 2007); however, slowed speech has been demonstrated to benefit older adults (Gordon-Salant et al, 2007;Adams et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These distance adjustments can be encapsulated in the signal-to-noise ratio, which is the difference in dB at a particular location between a sound of interest (signal) and the level of the noise. Good speech intelligibility requires about a +10dB signal-to-noise ratio (Adams & Moore, 2009;Dubbelboer & Houtgast, 2008).…”
Section: Perceiving Voice Environmental Factorsmentioning
confidence: 99%
“…However, the term noise has two general meanings; a narrow meaning and broader one. Noise in its narrow meaning, is a wideband sound consisting of infinite number of components with constant amplitudes and random phases (Adams & Moore, 2009). Such noise is referred to as physical noise.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted on the significance of signal-to-noise ratio (SNR) to the speech comprehension of normal listeners, as well as those who are hearing-impaired with and without hearing aids (Adams & Moore, 2009;Gengel, 1971;Finitzo-Hieber, & Tillman, 1978;Carhart & Tillman, 1970;Plomp, 1976;Sutter, 1985;Dirks et al, 1982;Schum, 1996;Cooper & Cutts, 1971;Killion, 1997). In these studies findings showed that SNR has a significant effect on speech intelligibility for both hearing impaired listeners and normal listeners.…”
Section: Introductionmentioning
confidence: 99%